2019
DOI: 10.21608/ajfs.2020.14239.1010
|View full text |Cite
|
Sign up to set email alerts
|

Improvement Phesio-Chemical Sensory and Microbiological Characters of Sweet Sorghum

Abstract: The present work was carried out to evaluate four types of sweet sorghum syrup made from Mn 4080 sweet sorghum variety either alone or with one of three herbal extracts (tumeric, cinnamon and ginger) for the physicochemical, sensory and microbiological properties.The results indicated that sweet sorghum syrup contained cinnamon extract had the highest percentages of sugar profile, tannins, total phenolics, antioxidant activity and minerals (K, Ca and Fe). Moreover, purity and the degree of browning and darkeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Evaluating the color parameters of sorghum jiggery was introduced in figure (4), which shows that the difference in the color intensity of the jiggery samples may be due to the difference in the sugar level, acidity, while the rise in the dark color was increased with increasing the sugar level and titratable acidity, which leads to the occurrence of (the maillard and caramel reaction that leads to a rise in 5-hydroxy Methylfurfura (HMF) content from non-enzymatic browning in sorghum syrup enhanced the rate of browning reaction. The results are in line with the findings reported by (Khalil et al, 2019). Also, regarding the palatability evaluation of jiggery cultivars (Rona and Brands) in 75 brix, a higher acceptance score was given compared to 85 brix with the same cultivars.…”
Section: Physicochemical Of Jiggerysupporting
confidence: 90%
See 1 more Smart Citation
“…Evaluating the color parameters of sorghum jiggery was introduced in figure (4), which shows that the difference in the color intensity of the jiggery samples may be due to the difference in the sugar level, acidity, while the rise in the dark color was increased with increasing the sugar level and titratable acidity, which leads to the occurrence of (the maillard and caramel reaction that leads to a rise in 5-hydroxy Methylfurfura (HMF) content from non-enzymatic browning in sorghum syrup enhanced the rate of browning reaction. The results are in line with the findings reported by (Khalil et al, 2019). Also, regarding the palatability evaluation of jiggery cultivars (Rona and Brands) in 75 brix, a higher acceptance score was given compared to 85 brix with the same cultivars.…”
Section: Physicochemical Of Jiggerysupporting
confidence: 90%
“…The chemical composition of sweet sorghum syrup is influenced by the type of variety, growing season, agroclimatic conditions and stage of maturity (Reddy et al, 2012). In the field of food processing, (Khalil et al, 2019) stated that sweet sorghum is a good source of syrup production and can be an attractive marketable product with different herbal flavors for all people who need to raise beneficial health while consuming it, as well as for the long shelf-life stability of syrup. On the other hand, (Makori, 2013) showed that higher glucose and fructose levels in sweet sorghum juice are better for producing good quality syrup.…”
Section: Introductionmentioning
confidence: 99%